Intracardiac Thrombosis and Coronary-to-Pulmonary Artery Fistula with Pulmonary Embolism and Budd-Chiari Syndrome in Behçet’s Disease: A Case Report - Tolga AKSU; Ayşegül ÖZ2 (Archives of Rheumatology, 2013)
Behçet’s disease (BD) is a multisystemic, chronic and inflammatory vasculitis presentation. A 29-year-old male patient with BD was admitted to our clinic with dyspnea and chest pain. On his physical examination, a left parasternal murmur resembling the sound of a machine was detected along with abdominal ascites. The patient’s electrocardiography and chest X-ray were normal. Thoracic computed tomography (CT) revealed a chronic pulmonary embolism. On abdominal CT, a thrombus was detected in the hepatic vein and inferior vena cava, which was consistent with Budd-Chiari syndrome (BCS). Twodimensional transthoracic echocardiography demonstrated a mass on the right atrium protruding into the right ventricle. On the suprasternal view, abnormal flow surrounding the arcus aorta and pulmonary artery was detected. Coronary angiography showed a fistula formation between the left main branch and pulmonary artery. A treatment with anti-inflammatory drugs and heparin was initiated. Complete recovery of the pulmonary embolism and intracardiac thrombosis were observed at six months. In this article, we present a BD patient with intracardiac thrombosis and coronary-to-pulmonary fistula associated with a pulmonary embolism and BCS.